Satisfacción con la vida y calidad de vida en usuarios del Centro Gerontológico Residencial Municipal Chambo, 2022 - Dayana Stefanía, Guerrero Cajo (2022)
ABSTRACT: This research was carried out at the Gerontological Center of the Municipal GAD in Chambo, during the period of November 2021 to March 2022, which aimed to relate life satisfaction and quality of life of users of the Municipal Residential Gerontological Center of Chambo. The research was bibliographical and documentary, with a cross-sectional design, correlational level and quantitative approach. The sample consisted of 100 medical records of older adults selected by non-probabilistic sampling whose ages range from 65 to 85 years. For data collection, an observation form was used to extract the results of the psychological instruments, the Satisfaction with Life Scale and the World Health Organization Quality of Life Assessment-Age from the clinical records. The most relevant results indicated that of the total population studied, 35% present dissatisfaction with life and 24% are slightly dissatisfied, as for the dimensions of quality of life, 38% show little functionality and 32% show neither good nor bad health, and in general 63% have poor quality of life. It is concluded that there is a significantly high positive correlation (r = 381**; p < 0.05) between satisfaction with life and quality of life, proving that the greater the satisfaction with life, the greater the presence of quality of life in adults